THE PSYCHOLOGICAL AND SOCIAL EFFECT OF CORONA PANDEMIC BETWEEN DIFFERENT CATEGORIES OF PEOPLE IN IRAQ (World Bulletin of Public Health, 2022)
The COVID-19 pandemic caused a significant shock to the world and its political, economic and health systems, as the world stood unable to take decisive decisions in order to eliminate the virus and neutralize its effects on various aspects of life. Complete or partial lockdown is the only way for many countries to prevent the spread of the new strain in the absence of an effective treatment and a vaccine for the disease, which caused different reactions among the world’s population between convinced of the existence of the virus and the feasibility of the lockdown as a safe means to prevent the spread of the disease and preserve lives, while others continue their lives and carry out their usual work and challenge the virus as a way of survival and continuity, and in light of these measures a clear repercussions appeared on all aspects of life. Also, the closure measures and stopping the wheel of the economy have caused a collapse in the economic systems, Many people are stunned by the loss of their livelihoods in a global economic and health crisis that the world has not witnessed before, This study use online questionnaire to collect opinions of different groups of society about the psychological and social effect of the new virus
Keywords: COVID-19; pandemic; Questionnaire